2013
DOI: 10.5402/2013/461704
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Treatment Failure among Pulmonary Tuberculosis Patients in Federal Medical Centre, Gombe, Northeastern Nigeria

Abstract: Treatment failure in patients with pulmonary tuberculosis poses a great danger to the global effort in control of tuberculosis. This study evaluated prevalence of treatment failure among pulmonary tuberculosis patients at Federal Medical Centre (FMC) Gombe, Nigeria. Consecutive patients managed between August 2008 and August 2009 at the Directly Observed Therapy (Tuberculosis) Unit of our hospital were enrolled for the study. Sputum specimens were collected from each patient at entry for Acid Fast Bacilli and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
4
5
1
1
Order By: Relevance
“…This is highly unsatisfactory as it is almost impossible to control TB if such a situation persists. A similarly high treatment failure rate was reported by Jibrin et al in the Northern part of the country [20]. Our study showed a significantly higher rate of treatment failure among the HIV-positive individuals when compared to their noninfected counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…This is highly unsatisfactory as it is almost impossible to control TB if such a situation persists. A similarly high treatment failure rate was reported by Jibrin et al in the Northern part of the country [20]. Our study showed a significantly higher rate of treatment failure among the HIV-positive individuals when compared to their noninfected counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that pulmonary tuberculosis affects mostly the most productive age group of the population unlike in developed countries where TB affects mostly the elderly (P D O Devies, 1999) which is similar with other the findings of other studies (Jibrin et al, 2013), , (Kochi 1999). These are active, skillful, experience and mobile individual that drive the economy of the developing nation (Armstrong 1995).…”
Section: Discussionsupporting
confidence: 87%
“…This will have positive effect on the compliance and reduce the chances of lost to follow-up. A similar finding was documented by (Jibrin et al, 2013). In some studies, the patients have to travel a distance of more than 7Km to the treatment centre and that implicate poor treatment outcome (Lisha et al, 2012), (Lake et al, 2011), (Babatunde et al, 2012).…”
supporting
confidence: 55%
“…Male subjects had a higher morbidity rate of 62% compared to 38% in Females, which not obey the national sex pattern. The overall cure rate of 5 studied years (83.56%) in our patients was slightly lower than 85% recommended by the world health organization target [28,29]. This means that more effort in needed to further improve of this cure rate by efficacious measures for follow up of patients.…”
Section: Discussioncontrasting
confidence: 52%